Impact of wild boar rooting on small forest‐dwelling rodents. Issue 4 (4th April 2020) - Mori, Emiliano; Ferretti, Francesco; Lagrotteria, Alessandro; La Greca, Leonardo; Solano, Emanuela; Fattorini, Niccolò
Abstract: Assessing impacts of wild boar on ecosystems is a research priority worldwide, with applied implications for environmental management. We evaluated whether rooting intensity by wild boar affected a rodent community in Central Italy. Rooting intensity was measured within trap transects and all around them, following standard procedures. We live‐trapped rodents in coppiced forests with a gradient of rooting intensity (including a fenced, boar‐proof, area) and evaluated relationships between abundance and rooting for two arboreal and five ground‐dwelling species. Among those, the most abundant ones were the bank vole Myodes glareolus and the yellow‐necked wood mouse Apodemus flavicollis. Rooting within and outside transects correlated to each other, as well as with the local passage rate of the wild boar, assessed through camera‐trapping. We found a negative relationship between rooting intensity and abundance of bank voles, that is, the main food resources of some predators of conservation concern. Rooting activity may trigger effects on ground‐dwelling rodents at the population level. Abstract : Evaluated whether rooting intensity by wild boar affected a rodent community in Central Italy. Live‐trapped rodents in coppiced forests with a gradient of rooting intensity (including a fenced, boar‐proof, area) and evaluated relationships between abundance and rooting for two arboreal and five ground‐dwelling species. Found a negative relationship between rooting intensity and abundance of bank voles, that is the main food resources of some predators of conservation concern.